Induction of non-apoptotic programmed cell death by oncogenic RAS in human epithelial cells and its suppression by MYC overexpression. (2nd November 2017) - Dendo, Kasumi; Yugawa, Takashi; Nakahara, Tomomi; Ohno, Shin-ichi; Goshima, Naoki; Arakawa, Hirofumi; Kiyono, Tohru
Abstract : In normal human epithelial cells, oncogenic RAS induces non-apoptotic PCD associated with macropinosome accumulation, which can be inhibited by MYC overexpression. This tumour suppressive pathway could be restored by MYC inhibition or rapamycin administration in cancer cells harbouring RAS mutations. Abstract: Oncogenic mutations of RAS genes, found in about 30% of human cancers, are considered to play important roles in cancer development. However, oncogenic RAS can also induce senescence in mouse and human normal fibroblasts. In some cell lines, oncogenic RAS has been reported to induce non-apoptotic programed cell death (PCD). Here, we investigated effects of oncogenic RAS expression in several types of normal human epithelial cells. Oncogenic RAS but not wild-type RAS stimulated macropinocytosis with accumulation of large-phase lucent vacuoles in the cytoplasm, subsequently leading to cell death which was indistinguishable from a recently proposed new type of PCD, methuosis. A RAC1 inhibitor suppressed accumulation of macropinosomes and overexpression of MYC attenuated oncogenic RAS-induced such accumulation, cell cycle arrest and cell death. MYC suppression or rapamycin treatment in some cancer cell lines harbouring oncogenic mutations in RAS genes induced cell death with accumulation of macropinosomes. These results suggest that this type of non-apoptotic PCD is a tumour-suppressing mechanism acting against oncogenic RAS mutations in normal human epithelial cells, which can be overcome by MYC overexpression, raising the possibility that its induction might be a novel approach to treatment of RAS-mutated human cancers.